2022
DOI: 10.3390/molecules27092798
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Extraction Efficiency of Flavonoids from Pyrus ussuriensis Leaves with Deep Eutectic Solvents

Abstract: In this study, deep eutectic solvents (DESs) were synthesized using different ratios of choline chloride (CC) and dicarboxylic acids, and their eutectic temperatures were determined. The DES synthesized using CC and glutaric acid (GA), which showed a higher extraction efficiency than conventional solvents, was used for the extraction of flavonoid components from Pyrus ussuriensis leaves (PUL), and the extraction efficiency was evaluated using the response surface methodology. The flavonoid components rutin, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Ginseng extracts prepared by various methods are reported to exhibit anti-inflammation activity by their suppression of both iNOS and COX-2 expressions [29]. This effect comes mostly from ginsenosides, the main ingredient in ginseng [7]. The antiinflammatory effect of GSD was shown via iNOS and NO but not COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginseng extracts prepared by various methods are reported to exhibit anti-inflammation activity by their suppression of both iNOS and COX-2 expressions [29]. This effect comes mostly from ginsenosides, the main ingredient in ginseng [7]. The antiinflammatory effect of GSD was shown via iNOS and NO but not COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…They are induced by lipopolysaccharides (LPSs), a major part of the gram-negative bacterial membrane, and adjust inflammation by discharging proinflammatory transmitter substances, such as inducible nitric oxide synthase (iNOS), prostaglandin E2 (PGE2), cyclooxygenase 2 (COX-2), tumor necrosis factor (TNF)-α, inter-leukin (IL)-1β, and IL-6 [4][5][6]. Imbalanced production of these transmitter substances results in chronic inflammatory disorders, such as various types of cancer, arteriosclerosis, diabetic nephropathy, and neurodegenerative diseases [7]. The pathological effects of inflammation on humans emphasize the need to develop safe and effective medicines that target various biochemical processes to reduce the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may be due to the target component dissolving faster over time, but prolonged extraction can lead to changes in the molecular structure of flavonoids (Akther et al, 2021). Lee et al (2022) and Xia et al (2021) showed a similar trend of increasing and then decreasing flavonoid yield with increasing extraction time when using microwave-assisted DES to extract flavonoids. Therefore, 70 min was considered the optimal extraction time and used for further experiments.…”
Section: Effect Of Extraction Time On the Yield Of Total Flavonoids F...mentioning
confidence: 99%
“…Lee et al [ 12 ] investigated the applications of deep eutectic solvents in extractions from natural leaves. They compared the efficiencies of various ratios of choline chloride and dicarboxylic acids for the extraction of flavonoid components from Pyrus ussuriensis leaves with respect to conventional solvents.…”
Section: Contributionsmentioning
confidence: 99%